Does teacher computer technology use perceived from TPCK frameworks stimulate student achievement in English language learning? - Rofiq, Annur; Widiati, Utami; Sulistyo, Teguh; Puspitasari, Yunita (Journal on English as a Foreign Language, 2024)
Studies on the relationship between teacher use of ICT and student achievement have been numerous, but those involving other intervening variables, such as technological, pedagogical, and content knowledge (TPCK), are still limited. This study examined the relationships between the use of computer technology (CT) by Indonesian EFL teachers and student achievement, taking into account the TPCK frameworks. Explanatory correlation serves as the research design, as this study was intended to explain the associations among variables under study. Data on teachers